World Building and Design of an Immersive Educational Escape Room: its Impact on Immersion - Ana Rita Bernardo Garcia (2022)
This dissertation focuses on world building and the process of designing an Immersive Educational Escape Room (IEER), what it consists of, and its impact over immersion. In this regard, this dissertation will approach the world design behind an IEER and its impact on players. The first stage will involve immersive experiment research. To ensure enough data to complement this project, we will be in direct contact with the IEER itself and a multidisciplinary team, allowing a later development of the next research stage, which will involve a different target. In addition to existing research about immersion, we aim to better understand how World Design affects immersion and how to approach adaptability issues towards educational games, specifically, photo sensibility and epilepsy. Hopefully, it will be possible to gather enough conclusions to encourage further discussion on the subject and further understanding of how Educational Escape Rooms can evolve.